FRAKSI BESI DAN PENGARUHNYA TERHADAP KELARUTAN POSFOR DI LAHAN RAWA (Iron Fraction And Its Effect On Posforning Sustainability In Rawa Land) - A, Fahmi (Universitas Palangka Raya, 2018)
ABSTRACT About 20 million Ha of tidal swampare found in Indonesia,6.7 million ha of them are acid sulphate soils which associated with peatland.Most of soil in tidal swamp are rich in iron, it potentialy toxic to the plant. We critically examine the presence of peat matter as surface layer to iron fraction and the role of ferrous to phosphorus (P) solubility in soil.Iron fractions analyzed in acid sulphate soil, peaty acid sulphate soil, shallow peatland, shallow peatland which all of peat layers were removed and shallow peatland which partially of peat layers were removed. Most of iron fraction in tidal swampland which covered by peat layer is organic-Fe form, the presence of peat layer on surface layer caused no correlation between Fe and P in soil. Key words : Acid sulphate soil, Iron, Peatland, Phosphorus andTidal swampland